Penerapan Problem-Based Learning Berbantuan Geogebra untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Materi Program Linear Kelas XI MIA-3 SMA Negeri 8 Mataram Tahun Ajaran 2024/2025 - Adawiyyah, Robi'atul Adawiyyah; Amrullah; Aiyub, Darma (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the learning outcomes of Grade XI MIA-3 students at SMA Negeri 8 Mataram on the topic of Linear Programming through the implementation of the Problem-Based Learning (PBL) model assisted by GeoGebra. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through learning achievement tests and classroom observation activities. The results showed that the application of PBL assisted by GeoGebra had a positive impact on students’ learning outcomes. The average score increased from 56.2 in the quiz to 65.8 in the first cycle and 79.2 in the second cycle. The percentage of learning mastery also improved from 30% before the intervention to 40% in the first cycle and 67% in the second cycle. The implementation of PBL encouraged students to think critically and solve problems, while GeoGebra helped them visualize mathematical concepts more concretely. Therefore, the use of Problem-Based Learning assisted by GeoGebra proved effective in enhancing students’ understanding and learning outcomes in Linear Programming.